HMGB1‐induced angiogenesis in perforated disc cells of human temporomandibular joint. Issue 2 (30th October 2017) - Feng, Yaping; Ke, Jin; Cao, Pinyin; Deng, Mohong; Li, Jian; Cai, Hengxing; Meng, Qinggong; Li, Yingjie; Long, Xing
Abstract: High mobility group 1 protein (HMGB1), a highly conserved nuclear DNA‐binding protein and inflammatory mediator, has been recently found to be involved in angiogenesis. Our previous study has demonstrated the elevation of HMGB1 in the tissue of perforated disc of temporomandibular joint (TMJ). Here, we investigated a novel mediator of HMGB1 in regulating hypoxia‐inducible factor‐1α (HIF‐1α) and vascular endothelial growth factor (VEGF) to mediate angiogenesis in perforated disc cells of TMJ. HMGB1 increased the expression of HIF‐1α and VEGF in a dose‐ and time‐dependent manner in these cells. Moreover, immunofluorescence assay exhibits that the HIF‐1α were activated by HMGB1. In addition, HMGB1 activated extracellular signal‐related kinase 1/2 (Erk1/2), Jun N‐terminal kinase (JNK), but not P38 in these cells. Furthermore, both U0126 (ErK inhibitor) and SP600125 (JNK inhibitor) significantly suppressed the enhanced production of HIF‐1α and VEGF induced by HMGB1. Tube formation of human umbilical vein endothelial cells (HUVECs) was significantly increased by exposure to conditioned medium derived from HMGB1‐stimulated perforated disc cells, while attenuated with pre‐treatment of inhibitors for VEGF, HIF‐1α, Erk and JNK, individually. Therefore, abundance of HMGB1 mediates activation of HIF‐1α in disc cells via Erk and JNK pathway and then, initiates VEGF secretion, thereby leading to disc angiogenesis and accelerating degenerative change of the perforated disc.